GAMBARAN PENGETAHUAN REMAJA PUTRI TENTANG USIA DAN JARAK KEHAMILAN - Muthia Utami; Iryanti Iryanti; Kamsatun Kamsatun; Susi Kusniasih (Politeknik Kesehatan Kemenkes Bandung, 2020)
ABSTRACT Maternal Mortality Rate in Indonesia is still relatively high, based on the Indonesia Demographic and Health Survey in 2012 showing a MMR of 359 / 100,000 live births. This figure is still far from the health development targets listed in the SDGs. In general, maternal mortality occurs due to bleeding during labor which can be caused by too young and too close pregnancy. This study aims to determine the description of knowledge of young women about age and distance of pregnancy. This type of research is Study Literature Review. Based on results of a journal search on age to get pregnant in the first journal 62.5% of young women are in category of insufficient knowledge, in the second journal 54.2%, both are due to a lack of information, in the third journal the educational factors are explained which influence the OR results = 3,437 and CI = 6,906-1,711). Based on a journal search on pregnancy spacing in the first journal 33.34% of young women lacked knowledge, in the second journal of 43.3%, both were caused by a lack of information, whereas in the third journal it was explained that educational factor had an effect of 51.9%. The results are obtained if knowledge of young women about age to get pregnant is still low with 62.5% and 43.4% lacking knowledge about pregnancy spacing. The need for an active role of health workers in providing counseling and socializing about the risk of pregnancy at a young age and the distance of pregnancy.